If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(4-2g)=40
We move all terms to the left:
5(4-2g)-(40)=0
We add all the numbers together, and all the variables
5(-2g+4)-40=0
We multiply parentheses
-10g+20-40=0
We add all the numbers together, and all the variables
-10g-20=0
We move all terms containing g to the left, all other terms to the right
-10g=20
g=20/-10
g=-2
| 1/2(11+8x)=3x-4 | | 7x+8x=350 | | 0.65*n=20.5 | | -8=-2(t-4) | | 2(x)+3(x)-x=54 | | -5x+12=2x+20-3x | | 4(w+2)-8w=-12 | | 5+3k=29 | | -3(2w-4)+7w=7(w+4) | | 28000+3000r=36000+2000;r=8 | | 10c-8=5c+32 | | 2*x-x+x+3*x-x=54 | | 7x-42+3x=7x+8+2 | | C=360*10/2x | | 5v-44=-3(v+4) | | 2x+3x-x=54 | | 4g+3=3g-0,5 | | 30=3(v+8)-6v | | -0.48x^2-2.54x-17.5=0 | | 5.3x-14.1=17.7 | | -10=-+7m | | X=y7 | | 3x-11/6=0 | | 4x-14=8+85 | | 3.6x-15.7=2.3 | | n^2-6n-40=(n-10)(n+) | | 7.9x-12.1=19.5 | | 2/4x-2=-6+5/12x | | 17.5-2.54x-0.48x^2=0 | | 2a-5=6a+13 | | p^2-7p-60=(p+5)(p-) | | (x)=x^2-2x |